Direct synthesis of 5-azapyrimidine 2′-deoxyribonucleosides. Hydrolysis of 5-aza-2′-deoxycytidine - Pískala, A. (Nucleic Acids Res, 1978)
The condensation of halogenose III with the triazines IV and VII was investigated. The course of the hydrolytical degradation of 5-aza-2′-deoxycytidine in acid, neutral and alkaline medium was established.